A Case Study of the Advent of Empirical Legal Studies in the Netherlands: The Narrow Pathway of Instrumentalism - Mascini, Peter (European Journal of Empirical Legal Studies, 2025)
This study examines how Empirical Legal Studies (ELS) gained a foothold in the Netherlands, particularly in the context of the country’s long tradition of empirical socio-legal research. It is based on participatory observation and content analysis. It is argued that the way in which ELS has developed in the Netherlands fits into a much longer intellectual tradition in which the instrumental study of law is central. This tradition largely ignores alternative approaches, also prevalent in the Netherlands, in which the relationship between law and other normative systems (’legal pluralism’) or between law and society is central. While these differences in the empirical study of law, which previously divided the Dutch L&S community to the bone, have become more or less invisible with the hospitable reception ELS has received from the L&S community, substantive differences remain. Bringing these differences back to the fore may help to avoid misunderstandings that arise from ignorance of the coexistence of different empirical approaches to the study of law and may facilitate the conscious choice of a particular approach.